A direct association between suicide and reduced amygdala volume: A retrospective study - Emre, Elif; Yildiz, Sevler; Rumeysa Yaman Baran, Ayse; Kilicarslan, Gulhan; Aydin, Suna; Agirbas, Esra Piril; Aydin, Suleyman (Sage Publications Ltd, 2025)
Objective The neurological causes of suicide remain poorly understood. This study sought to ascertain whether there is a correlation between amygdala volume and suicidal behavior.Methods This case-control retrospective study included 193 participants-108 healthy controls and 85 individuals with a history of suicide attempts. Sagittal magnetic resonance imaging was conducted for each participant, and cross-sectional areas of the left and right amygdala were determined independently using freehand tracing. The total volume of the amygdala was determined by multiplying the thickness of the slices by the sum of the regions.Results Patients with a history of suicide attempts had significantly decreased amygdala volumes on both the right (p = 0.018) and left (p = 0.036) sides compared with controls. Receiver operating characteristic analysis determined a cutoff value of 1825 mm(3) for both hemispheres. The cutoff sensitivity and specificity for the right amygdala were 30.6% and 88%, whereas the values for the left amygdala were 31.8% and 84.3%, respectively.Conclusions This is the first study to show that individuals who had attempted suicide had considerably decreased left and right amygdala volumes, with receiver operating characteristic analysis indicating good specificity (84.3%-88%). According to these findings, a reduced amygdala volume might be a useful biomarker for identifying those who are at risk of attempting suicide.
Keywords: Amygdala volume; suicide attempt; magnetic resonance imaging; suicidal behavior; neurobiological causes